PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING (SAW) PADA SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN RUKUN WARGA TERBAIK KELURAHAN JATIMULYA - Hernalom Sitorus; Muhammad Adhitya Nugroho (JURNAL SATYA INFORMATIKA, 2022)
Urban village (kelurahan) Jatimulya has 19 hamlet (rukun warga/rw) who have the task of assisting the urban village in running the government system, in order to improve and supervise services in the community, the kelurahan conducts performance evaluations to find the best hamlet, but in the implementation of these evaluations it often causes debate because the community pillars evaluated are only based on community complaints report and not comprehensive, besides the evaluation does not have a clear value indicator so that the village can not oversee the extent to which the planned activities and programs are running well or not. Based on this, the village wants a way to evaluate the performance of the community pillars thoroughly and have clear assessment indicators so that they can be used as benchmarks to improve services in the community. The problem with this research is that there is no specific method used by the head of the government and kelurahan to evaluate the performance of the community's pillars. This study uses the Simple Additive Weighting (SAW) method where this method is a way to find optimal alternatives from a number of alternatives with certain criteria. The conclusions of the results of this study were to obtain the value of performance and the ranking of a pillar of citizens which was applied for transparency of the assessment.